(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Now days, every company is facing data leakage. That is very serious problem faced by company. An owner of enterprise has given confidential data to its employee but most of the time employee leaks the data. That leak data found in illegal place such as on the web of comparator enterprise or on laptop of employee of comparator enterprise or the owner of Comparators Companyâ€™s laptop. It May or may not be observed by owner. Leak data may be basic code or design provision, cost lists, rational property and copy rights data, trade secrets, forecasts and budgets. In this case the data leaked out it leaves the company goes in undefended the authority of the corporation. This uninhibited data leakage puts business in a back in position. To find the solution on this problem we develop two models. First, when any employee of enterprise access confidential data without the consent of owner in that case ,we developed data watcher model to identifying data leaker and suppose employee given data outside the enterprise for that we devolved second model for assessing the â€œguiltâ€ of agents. Guilt model are used to improve the probability of identifying guilty third parties.